A lightweight and high heat dissipation PC composite material and preparation method thereof
The high-definition structure and nanopore microporous structure are formed by using foam aluminum nitride particles with silver nanowires on the surface and the inner thermal conductivity layer of nanodiamond and the outer heat dissipation layer prepared by electrospinning in polymer materials. The problem of insufficient thermal conductivity of molecular materials has achieved efficient thermal conductivity and heat dissipation effects.
Patent Information
- Application Number
- CN202410539168.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-04-30
AI Technical Summary
The thermal conductivity of polymer materials is poorer than that of metal materials, which limits its widespread use in heat dissipation applications. The thermal conductivity and heat dissipation properties are not the same. It is necessary to improve the type and structure of fillers to improve the thermal conductivity and heat dissipation properties.
The structure of the inner thermal conductivity layer and the outer heat dissipation layer is composed of foam aluminum nitride particles and nanodiamonds with silver nanowires on the surface to form a triple composite structure. The outer layer is prepared by electrospinning method to form nanopores and micropores. Pore structure for rapid heat dissipation.
High thermal conductivity and high heat dissipation are achieved, and the thermal conductivity effect is maximized through the "large network heat channel" and "small network heat channel" structures, and rapid heat dissipation is achieved through the structure of nanopores and micropores.
Smart Images

Figure BDA0004820555770000081 
Figure BDA0004820555770000101
Abstract
Description
Technical Field
[0001] The present invention relates to the field of functional composite materials, and in particular to a lightweight and high-heat dissipation PC composite material and a preparation method thereof. Background Art
[0002] Polymer materials are widely used in the fields of chemical industry, energy, electronic device heat dissipation, electronic information, electrical engineering, aerospace, etc. due to their good corrosion resistance, low price, light weight and easy processing and molding, and show broad application prospects. The thermal conductivity of polymer materials is still far behind that of metal materials. Therefore, the application of polymer materials in many aspects is limited to a certain extent. However, this problem is effectively solved by adding different high thermal conductivity fillers (such as graphite, nanographite sheets, metal powders, carbon nanotubes, etc.) to blend and modify polymer materials. Since the formation of the thermal conductive network and the size of the interfacial thermal resistance are the key factors affecting the thermal conductivity of the filled polymer, the type and structure of the added filler become particularly important in the process of studying polymer materials. Having thermal conductivity at the same time does not mean good heat dissipation. To achieve high heat dissipation effect, it must have good thermal conductivity and good heat dissipation. Summary of the invention
[0003] Technical problem to be solved: The purpose of the present invention is to provide a lightweight and high-heat dissipation PC composite material and a preparation method thereof, comprising an inner heat-conducting layer and an outer heat-dissipating layer, the inner heat-conducting layer having good thermal conductivity, and foamed aluminum nitride particles and nano-diamonds having silver nanowires on the surface are added, the foamed aluminum nitride particles having silver nanowires on the surface have both a three-dimensional structure and a two-dimensional linear structure, the nano-diamonds have a point structure, realizing a triple composite structure of points, lines and surfaces, the lines and surfaces are overlapped to form a "large network heat channel", and the points and lines are overlapped to form a "small network heat channel", thereby achieving the thermal conductivity effect to the greatest extent.
[0004] Technical solution: A lightweight and high heat dissipation PC composite material, comprising an inner heat conductive layer and an outer heat dissipation layer; the inner heat conductive layer has a thickness of 0.5-3.0 mm, and the outer heat dissipation layer has a thickness of 0.05-0.1 mm of the inner heat dissipation layer.
[0005] Furthermore, the preparation method of the inner heat conductive layer is as follows:
[0006] Step 1: Mix the foamed aluminum nitride particles with silver nanowires on the surface and nanodiamonds, add the hydrolyzed silane coupling agent, and stir to react for 4-5 hours;
[0007] Step 2: Filter and dry to obtain mixed filler;
[0008] Step 3: Dry 100 parts of PC and 35 parts of ABS, add 10-15 parts of mixed filler and 5 parts of magnesium stearate, and mix well in a high-speed mixer;
[0009] Step 4: Extrusion granulation through a twin-screw extruder, the extrusion temperature is 220-250°C, the screw speed is 60r / min, and lightweight and high thermal conductivity granules are obtained;
[0010] Step 5: Dry at 100°C, and inject through an injection machine at an injection temperature of 225-260°C to obtain an inner heat conductive layer.
[0011] Furthermore, the preparation method of the foamed aluminum nitride particles having silver nanowires on the surface is as follows:
[0012] (1) 10 parts of 0.5 mmol / L silver nitrate aqueous solution and 10 parts of 0.5 mmol / L sodium citrate aqueous solution were mixed, stirred vigorously, and 0.6 parts of 10 mmol / L sodium borohydride solution were quickly added. Stirring was stopped after 30 seconds to obtain a silver nanoparticle suspension with a diameter of 2-6 nm;
[0013] (2) Take 3 parts of foamed aluminum nitride particles, add them into 150 parts of a mixed solution of 1 mmol / L silver nitrate and 2 mmol / L polyvinyl pyrrolidone, and stir evenly;
[0014] (3) adding 5-7 parts of silver nanoparticle suspension and stirring for 0.5 h;
[0015] (4) Exposure to a 15 W low-pressure mercury lamp with a wavelength of 253.7 nm for 48 h;
[0016] (5) Filtering to obtain foamed aluminum nitride particles with silver nanowires on the surface.
[0017] Furthermore, in step 1, the mass ratio of the foamed aluminum nitride particles having silver nanowires on the surface to the nano-diamonds is (1-2):1.
[0018] Furthermore, the foamed aluminum nitride particles have a particle size of 10-50 μm and a porosity of 74-76%.
[0019] A method for preparing a lightweight and high heat dissipation PC composite material, the preparation steps are as follows:
[0020] Step 1: Dissolve 10-15 parts of PC in 100 parts of chloroform, add 1-2 parts of nano calcium carbonate, stir for 3-4 hours to obtain electrospinning solution;
[0021] Step 2: transferring the electrospinning solution to an electrospinning device, and performing electrospinning with the inner heat conductive layer as a receiving plate, wherein the receiving spinning surface of the inner heat conductive layer is coated with a hydrophilic adhesive added with nano-diamonds, and curing and drying at 60-80° C. for 10-18 hours to obtain a composite material including an inner heat conductive layer and an outer layer;
[0022] Step 3: Treat the outer layer with dilute hydrochloric acid to remove the nano-calcium carbonate, and obtain an outer heat dissipation layer having both nanopores and micropores, thereby obtaining a lightweight and high heat dissipation PC composite material.
[0023] Furthermore, the particle size of the nano calcium carbonate is 30-60 nm.
[0024] Further, the electrospinning parameters are: the spinning temperature is 22-28°C, the spinning voltage is 14-18kV, the relative humidity is 40-50%, the receiving distance between the receiving plate and the electrospinning nozzle device is 10-14cm, and the spinning solution flow rate is 1.0-1.5mL / h. Further, the mass volume ratio of nanodiamonds to hydrophilic adhesive in the hydrophilic adhesive added with nanodiamonds is (3-5)g:80mL.
[0025] Furthermore, the inner diameter of the electrospinning nozzle is 0.4-0.6 mm.
[0026] Beneficial effects:
[0027] 1. The lightweight and high-heat dissipation PC composite material of the present invention comprises an inner heat-conducting layer and an outer heat-dissipating layer. The inner heat-conducting layer has good thermal conductivity, and foamed aluminum nitride particles with silver nanowires on the surface and nano-diamonds are added. The foamed aluminum nitride particles with silver nanowires on the surface have both a three-dimensional structure and a two-dimensional linear structure. The nano-diamonds have a point structure, realizing a three-fold composite structure of points, lines and surfaces. The lines and surfaces are overlapped to form a "large network heat channel", and the points and lines are overlapped to form a "small network heat channel", thereby achieving the thermal conductivity effect to the greatest extent.
[0028] 2. The foamed aluminum nitride particles of the present invention have high porosity and light weight, and not only have high thermal conductivity, but also have high emissivity and good heat dissipation effect.
[0029] 3. The outer heat dissipation layer used in the present invention is obtained by electrospinning. The outer layer obtained by electrospinning has a micron pore structure. After removing the nano-calcium carbonate, a rough structure with both nanopores and micropores is obtained, thereby obtaining a high emissivity. When heat is transferred from the inner heat conductive layer to the outer heat dissipation layer, the effect of rapid heat dissipation can be achieved.
[0030] 4. The present invention uses a hydrophilic adhesive with nano-diamonds added to bond the inner thermal conductive layer and the outer heat dissipation layer. After the outer layer receives heat, moisture enters the inner layer through nanopores and micropores, and then reaches the thermal conductive layer through the hydrophilic adhesive. In the high temperature environment of the thermal conductive layer, water droplets evaporate easily, taking away heat, further playing a role in cooling and dissipating heat. DETAILED DESCRIPTION
[0031] The present invention proposes a lightweight and high heat dissipation PC composite material and a preparation method thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention will be further described in detail with reference to the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] Example 1
[0033] The preparation method of foamed aluminum nitride is as follows:
[0034] (1) 1.5 g of anhydrous aluminum chloride, 2.5 g of sodium azide, and 0.2 g of nano sodium chloride were placed in a stainless steel reactor in a glove box filled with N2, and deoxygenated with ferrous sulfate for 2 h;
[0035] (2) After sealing, place in an atmosphere sintering furnace and sinter at a furnace temperature of 550°C for 3 hours;
[0036] (3) taking out the reactor, cooling it to room temperature, removing the nano sodium chloride and byproduct sodium chloride with deionized water, and drying;
[0037] (4) After grinding, filtering, casting and pressing, placing it in an atmosphere sintering furnace again, using argon as a protective gas, sintering at a furnace temperature of 1300°C for 3 hours, and naturally cooling to room temperature to obtain the product.
[0038] It was determined that the particle size was 10-50 μm and the average porosity was 75.7%.
[0039] Example 2
[0040] The preparation method of the inner heat conductive layer is as follows:
[0041] Step 1: Mix foamed aluminum nitride particles with silver nanowires on the surface and nanodiamonds in a mass ratio of 1:1, add a hydrolyzed silane coupling agent, and stir to react for 4 hours;
[0042] Step 2: Filter and dry to obtain mixed filler;
[0043] Step 3: Dry 100 parts of PC and 35 parts of ABS, add 13 parts of mixed filler and 5 parts of magnesium stearate, and mix well in a high-speed mixer;
[0044] Step 4: Extrusion granulation through a twin-screw extruder, the extrusion temperature is 240°C, the screw speed is 60r / min, and lightweight and high thermal conductivity granules are obtained;
[0045] Step 5: Dry at 100°C, and inject through an injection molding machine at an injection temperature of 250°C to obtain an inner thermal conductive layer with a thickness of 2.0 mm. The preparation method of foamed aluminum nitride particles with silver nanowires on the surface is as follows:
[0046] (1) 10 parts of 0.5 mmol / L silver nitrate aqueous solution and 10 parts of 0.5 mmol / L sodium citrate aqueous solution were mixed, stirred vigorously, and 0.6 parts of 10 mmol / L sodium borohydride solution were quickly added. Stirring was stopped after 30 seconds to obtain a silver nanoparticle suspension with a diameter of 2-6 nm;
[0047] (2) Take 3 parts of foamed aluminum nitride particles, add them into 150 parts of a mixed solution of 1 mmol / L silver nitrate and 2 mmol / L polyvinyl pyrrolidone, and stir evenly;
[0048] (3) adding 6 parts of silver nanoparticle suspension and stirring for 0.5 h;
[0049] (4) Exposure to a 15 W low-pressure mercury lamp with a wavelength of 253.7 nm for 48 h;
[0050] (5) Filtering to obtain foamed aluminum nitride particles with silver nanowires on the surface.
[0051] Example 3
[0052] The preparation method of the inner heat conductive layer is as follows:
[0053] Step 1: Mix foamed aluminum nitride particles with silver nanowires on the surface and nanodiamonds in a mass ratio of 1:2, add a hydrolyzed silane coupling agent, and stir to react for 4 hours;
[0054] Step 2: Filter and dry to obtain mixed filler;
[0055] Step 3: Dry 100 parts of PC and 35 parts of ABS, add 13 parts of mixed filler and 5 parts of magnesium stearate, and mix well in a high-speed mixer;
[0056] Step 4: Extrusion granulation through a twin-screw extruder, the extrusion temperature is 240°C, the screw speed is 60r / min, and lightweight and high thermal conductivity granules are obtained;
[0057] Step 5: Dry at 100°C, and inject through an injection molding machine at an injection temperature of 250°C to obtain an inner thermal conductive layer with a thickness of 2.0 mm. The preparation method of foamed aluminum nitride particles with silver nanowires on the surface is as follows:
[0058] (1) 10 parts of 0.5 mmol / L silver nitrate aqueous solution and 10 parts of 0.5 mmol / L sodium citrate aqueous solution were mixed, stirred vigorously, and 0.6 parts of 10 mmol / L sodium borohydride solution were quickly added. Stirring was stopped after 30 seconds to obtain a silver nanoparticle suspension with a diameter of 2-6 nm;
[0059] (2) Take 3 parts of foamed aluminum nitride particles, add them into 150 parts of a mixed solution of 1 mmol / L silver nitrate and 2 mmol / L polyvinyl pyrrolidone, and stir evenly;
[0060] (3) adding 6 parts of silver nanoparticle suspension and stirring for 0.5 h;
[0061] (4) Exposure to a 15 W low-pressure mercury lamp with a wavelength of 253.7 nm for 48 h;
[0062] (5) Filtering to obtain foamed aluminum nitride particles with silver nanowires on the surface.
[0063] Example 4
[0064] The preparation method of the inner heat conductive layer is as follows:
[0065] Step 1: Mix foamed aluminum nitride particles with silver nanowires on the surface and nanodiamonds in a mass ratio of 1:2, add a hydrolyzed silane coupling agent, and stir to react for 4 hours;
[0066] Step 2: Filter and dry to obtain mixed filler;
[0067] Step 3: Dry 100 parts of PC and 35 parts of ABS, add 10 parts of mixed filler and 5 parts of magnesium stearate, and mix well in a high-speed mixer;
[0068] Step 4: Extrusion granulation through a twin-screw extruder, the extrusion temperature is 240°C, the screw speed is 60r / min, and lightweight and high thermal conductivity granules are obtained;
[0069] Step 5: Dry at 100°C, and inject through an injection molding machine at an injection temperature of 250°C to obtain an inner thermal conductive layer with a thickness of 2.0 mm. The preparation method of foamed aluminum nitride particles with silver nanowires on the surface is as follows:
[0070] (1) 10 parts of 0.5 mmol / L silver nitrate aqueous solution and 10 parts of 0.5 mmol / L sodium citrate aqueous solution were mixed, stirred vigorously, and 0.6 parts of 10 mmol / L sodium borohydride solution were quickly added. Stirring was stopped after 30 seconds to obtain a silver nanoparticle suspension with a diameter of 2-6 nm;
[0071] (2) Take 3 parts of foamed aluminum nitride particles, add them into 150 parts of a mixed solution of 1 mmol / L silver nitrate and 2 mmol / L polyvinyl pyrrolidone, and stir evenly;
[0072] (3) adding 6 parts of silver nanoparticle suspension and stirring for 0.5 h;
[0073] (4) Exposure to a 15 W low-pressure mercury lamp with a wavelength of 253.7 nm for 48 h;
[0074] (5) Filtering to obtain foamed aluminum nitride particles with silver nanowires on the surface.
[0075] Example 5
[0076] The preparation method of the inner heat conductive layer is as follows:
[0077] Step 1: Mix foamed aluminum nitride particles with silver nanowires on the surface and nanodiamonds in a mass ratio of 1:2, add a hydrolyzed silane coupling agent, and stir to react for 4 hours;
[0078] Step 2: Filter and dry to obtain mixed filler;
[0079] Step 3: Dry 100 parts of PC and 35 parts of ABS, add 15 parts of mixed filler and 5 parts of magnesium stearate, and mix well in a high-speed mixer;
[0080] Step 4: Extrusion granulation through a twin-screw extruder, the extrusion temperature is 240°C, the screw speed is 60r / min, and lightweight and high thermal conductivity granules are obtained;
[0081] Step 5: Dry at 100°C, and inject through an injection molding machine at an injection temperature of 250°C to obtain an inner thermal conductive layer with a thickness of 2.0 mm. The preparation method of foamed aluminum nitride particles with silver nanowires on the surface is as follows:
[0082] (1) 10 parts of 0.5 mmol / L silver nitrate aqueous solution and 10 parts of 0.5 mmol / L sodium citrate aqueous solution were mixed, stirred vigorously, and 0.6 parts of 10 mmol / L sodium borohydride solution were quickly added. Stirring was stopped after 30 seconds to obtain a silver nanoparticle suspension with a diameter of 2-6 nm;
[0083] (2) Take 3 parts of foamed aluminum nitride particles, add them into 150 parts of a mixed solution of 1 mmol / L silver nitrate and 2 mmol / L polyvinyl pyrrolidone, and stir evenly;
[0084] (3) adding 6 parts of silver nanoparticle suspension and stirring for 0.5 h;
[0085] (4) Exposure to a 15 W low-pressure mercury lamp with a wavelength of 253.7 nm for 48 h;
[0086] (5) Filtering to obtain foamed aluminum nitride particles with silver nanowires on the surface.
[0087] Example 6
[0088] The preparation method of the inner heat conductive layer is as follows:
[0089] Step 1: Mix foamed aluminum nitride particles with silver nanowires on the surface and nanodiamonds in a mass ratio of 1:2, add a hydrolyzed silane coupling agent, and stir to react for 4 hours;
[0090] Step 2: Filter and dry to obtain mixed filler;
[0091] Step 3: Dry 100 parts of PC and 35 parts of ABS, add 13 parts of mixed filler and 5 parts of magnesium stearate, and mix well in a high-speed mixer;
[0092] Step 4: Extrusion granulation through a twin-screw extruder, the extrusion temperature is 240°C, the screw speed is 60r / min, and lightweight and high thermal conductivity granules are obtained;
[0093] Step 5: Dry at 100°C, and inject through an injection molding machine at an injection temperature of 250°C to obtain an inner thermal conductive layer with a thickness of 2.0 mm. The preparation method of foamed aluminum nitride particles with silver nanowires on the surface is as follows:
[0094] (1) 10 parts of 0.5 mmol / L silver nitrate aqueous solution and 10 parts of 0.5 mmol / L sodium citrate aqueous solution were mixed, stirred vigorously, and 0.6 parts of 10 mmol / L sodium borohydride solution were quickly added. Stirring was stopped after 30 seconds to obtain a silver nanoparticle suspension with a diameter of 2-6 nm;
[0095] (2) Take 3 parts of foamed aluminum nitride particles, add them into 150 parts of a mixed solution of 1 mmol / L silver nitrate and 2 mmol / L polyvinyl pyrrolidone, and stir evenly;
[0096] (3) adding 5 parts of silver nanoparticle suspension and stirring for 0.5 h;
[0097] (4) Exposure to a 15 W low-pressure mercury lamp with a wavelength of 253.7 nm for 48 h;
[0098] (5) Filtering to obtain foamed aluminum nitride particles with silver nanowires on the surface.
[0099] Example 7
[0100] The preparation method of the inner heat conductive layer is as follows:
[0101] Step 1: Mix foamed aluminum nitride particles with silver nanowires on the surface and nanodiamonds in a mass ratio of 1:2, add a hydrolyzed silane coupling agent, and stir to react for 4 hours;
[0102] Step 2: Filter and dry to obtain mixed filler;
[0103] Step 3: Dry 100 parts of PC and 35 parts of ABS, add 13 parts of mixed filler and 5 parts of magnesium stearate, and mix well in a high-speed mixer;
[0104] Step 4: Extrusion granulation through a twin-screw extruder, the extrusion temperature is 240°C, the screw speed is 60r / min, and lightweight and high thermal conductivity granules are obtained;
[0105] Step 5: Dry at 100°C, and inject through an injection molding machine at an injection temperature of 250°C to obtain an inner thermal conductive layer with a thickness of 2.0 mm. The preparation method of foamed aluminum nitride particles with silver nanowires on the surface is as follows:
[0106] (1) 10 parts of 0.5 mmol / L silver nitrate aqueous solution and 10 parts of 0.5 mmol / L sodium citrate aqueous solution were mixed, stirred vigorously, and 0.6 parts of 10 mmol / L sodium borohydride solution were quickly added. Stirring was stopped after 30 seconds to obtain a silver nanoparticle suspension with a diameter of 2-6 nm;
[0107] (2) Take 3 parts of foamed aluminum nitride particles, add them into 150 parts of a mixed solution of 1 mmol / L silver nitrate and 2 mmol / L polyvinyl pyrrolidone, and stir evenly;
[0108] (3) adding 7 parts of silver nanoparticle suspension and stirring for 0.5 h;
[0109] (4) Exposure to a 15 W low-pressure mercury lamp with a wavelength of 253.7 nm for 48 h;
[0110] (5) Filtering to obtain foamed aluminum nitride particles with silver nanowires on the surface.
[0111] Comparative Example 1
[0112] The difference between this comparative example and Example 3 is that the surface of the added foamed aluminum nitride particles does not have silver nanowires, as follows:
[0113] The preparation method of the inner heat conductive layer is as follows:
[0114] Step 1: Mix foamed aluminum nitride particles and nanodiamonds in a mass ratio of 1:2, add hydrolyzed silane coupling agent, and stir to react for 4 hours;
[0115] Step 2: Filter and dry to obtain mixed filler;
[0116] Step 3: Dry 100 parts of PC and 35 parts of ABS, add 13 parts of mixed filler and 5 parts of magnesium stearate, and mix well in a high-speed mixer;
[0117] Step 4: Extrusion granulation through a twin-screw extruder, the extrusion temperature is 240°C, the screw speed is 60r / min, and lightweight and high thermal conductivity granules are obtained;
[0118] Step 5: Dry at 100°C, and use an injection molding machine with an injection temperature of 250°C to obtain an inner heat conductive layer with a thickness of 2.0 mm.
[0119] Comparative Example 2
[0120] The difference between this comparative example and Example 3 is that no nano diamond is added, specifically as follows:
[0121] The preparation method of the inner heat conductive layer is as follows:
[0122] Step 1: Take foamed aluminum nitride particles with silver nanowires on the surface, add hydrolyzed silane coupling agent, and stir to react for 4 hours; Step 2: Filter and dry to obtain modified filler;
[0123] Step 3: Dry 100 parts of PC and 35 parts of ABS, add 13 parts of modified filler and 5 parts of magnesium stearate, and mix well in a high-speed mixer;
[0124] Step 4: Extrusion granulation through a twin-screw extruder, the extrusion temperature is 240°C, the screw speed is 60r / min, and lightweight and high thermal conductivity granules are obtained;
[0125] Step 5: Dry at 100°C, and inject through an injection molding machine at an injection temperature of 250°C to obtain an inner thermal conductive layer with a thickness of 2.0 mm. The preparation method of foamed aluminum nitride particles with silver nanowires on the surface is as follows:
[0126] (1) 10 parts of 0.5 mmol / L silver nitrate aqueous solution and 10 parts of 0.5 mmol / L sodium citrate aqueous solution were mixed, stirred vigorously, and 0.6 parts of 10 mmol / L sodium borohydride solution were quickly added. Stirring was stopped after 30 seconds to obtain a silver nanoparticle suspension with a diameter of 2-6 nm;
[0127] (2) Take 3 parts of foamed aluminum nitride particles, add them into 150 parts of a mixed solution of 1 mmol / L silver nitrate and 2 mmol / L polyvinyl pyrrolidone, and stir evenly;
[0128] (3) adding 6 parts of silver nanoparticle suspension and stirring for 0.5 h;
[0129] (4) Exposure to a 15 W low-pressure mercury lamp with a wavelength of 253.7 nm for 48 h;
[0130] (5) Filtering to obtain foamed aluminum nitride particles with silver nanowires on the surface.
[0131] The above examples were all prepared into samples with a thickness of 2.0 mm, a length of 5 cm and a width of 5 cm, and the thermal conductivity was measured according to GB / T3399-1982.
[0132] The tensile properties were tested according to GB / T 1040-2018, the tensile rate was 50 mm / min, and the sample was treated at a constant temperature and humidity for 24 hours; the simply supported beam notched impact strength was tested according to GB / T 1043-2008, the notch was type A, and the sample was treated at a constant temperature and humidity for 24 hours. The results are shown in Table 1 below:
[0133] Table 1
[0134]
[0135] After comprehensive consideration of thermal conductivity and mechanical properties, Example 3 was selected for subsequent tests.
[0136] Example 8
[0137] A method for preparing a lightweight and high heat dissipation PC composite material, the preparation steps are as follows:
[0138] Step 1: Take 10 parts of PC and dissolve them in 100 parts of chloroform, add 1 part of nano calcium carbonate with a particle size of 30-60nm, stir for 3h, and obtain electrospinning solution;
[0139] Step 2: Transfer the electrospinning solution to the electrospinning device, and use the inner heat conductive layer as the receiving plate for electrospinning. The electrospinning parameters are as follows: the spinning temperature is 25°C, the spinning voltage is 14kV, the relative humidity is 45%, the receiving distance between the receiving plate and the electrospinning nozzle device is 10cm, the inner diameter of the electrospinning nozzle is 0.4mm, the spinning solution flow rate is 1.0mL / h, and the inner heat conductive layer receiving spinning surface is coated with an aqueous polyurethane adhesive with nanodiamonds added thereto, the mass volume ratio of nanodiamonds to aqueous polyurethane adhesive is 3g:80mL, and the composite material including the inner heat conductive layer and the outer layer is obtained by curing and drying at 70°C for 15h;
[0140] Step 3: Treat the outer layer with dilute hydrochloric acid to remove the nano-calcium carbonate, and obtain an outer heat dissipation layer having both nanopores and micropores, thereby obtaining a lightweight and high heat dissipation PC composite material.
[0141] Example 9
[0142] A method for preparing a lightweight and high heat dissipation PC composite material, the preparation steps are as follows:
[0143] Step 1: Take 12 parts of PC and dissolve it in 100 parts of chloroform, add 2 parts of nano calcium carbonate with a particle size of 30-60nm, stir for 3h, and obtain electrospinning solution;
[0144] Step 2: Transfer the electrospinning solution to the electrospinning device, and use the inner heat conductive layer as the receiving plate for electrospinning. The electrospinning parameters are as follows: the spinning temperature is 25°C, the spinning voltage is 16 kV, the relative humidity is 45%, the receiving distance between the receiving plate and the electrospinning nozzle device is 12 cm, the inner diameter of the electrospinning nozzle is 0.5 mm, the spinning solution flow rate is 1.2 mL / h, and the inner heat conductive layer receiving spinning surface is coated with an aqueous polyurethane adhesive with nanodiamonds added thereto, the mass volume ratio of nanodiamonds to aqueous polyurethane adhesive is 4 g:80 mL, and the composite material including the inner heat conductive layer and the outer layer is obtained by curing and drying at 70°C for 15 hours;
[0145] Step 3: Treat the outer layer with dilute hydrochloric acid to remove the nano-calcium carbonate, and obtain an outer heat dissipation layer having both nanopores and micropores, thereby obtaining a lightweight and high heat dissipation PC composite material.
[0146] Example 10
[0147] A method for preparing a lightweight and high heat dissipation PC composite material, the preparation steps are as follows:
[0148] Step 1: Take 14 parts of PC and dissolve it in 100 parts of chloroform, add 2 parts of nano calcium carbonate with a particle size of 30-60nm, stir for 4 hours, and obtain an electrospinning solution;
[0149] Step 2: Transfer the electrospinning solution to the electrospinning device, and use the inner heat conductive layer as the receiving plate for electrospinning. The electrospinning parameters are as follows: the spinning temperature is 25°C, the spinning voltage is 16 kV, the relative humidity is 45%, the receiving distance between the receiving plate and the electrospinning nozzle device is 12 cm, the inner diameter of the electrospinning nozzle is 0.5 mm, the spinning solution flow rate is 1.4 mL / h, and the inner heat conductive layer receiving spinning surface is coated with an aqueous polyurethane adhesive with nanodiamonds added thereto, the mass volume ratio of nanodiamonds to aqueous polyurethane adhesive is 4 g:80 mL, and the composite material including the inner heat conductive layer and the outer layer is obtained by curing and drying at 70°C for 15 h.
[0150] Step 3: Treat the outer layer with dilute hydrochloric acid to remove the nano-calcium carbonate, and obtain an outer heat dissipation layer having both nanopores and micropores, thereby obtaining a lightweight and high heat dissipation PC composite material.
[0151] Embodiment 11
[0152] A method for preparing a lightweight and high heat dissipation PC composite material, the preparation steps are as follows:
[0153] Step 1: Take 15 parts of PC and dissolve it in 100 parts of chloroform, add 2 parts of nano calcium carbonate with a particle size of 30-60nm, stir for 4 hours, and obtain an electrospinning solution;
[0154] Step 2: Transfer the electrospinning solution to the electrospinning device, and use the inner heat conductive layer as the receiving plate for electrospinning. The electrospinning parameters are as follows: the spinning temperature is 25°C, the spinning voltage is 18kV, the relative humidity is 45%, the receiving distance between the receiving plate and the electrospinning nozzle device is 14cm, the inner diameter of the electrospinning nozzle is 0.6mm, the spinning solution flow rate is 1.5mL / h, and the inner heat conductive layer receiving spinning surface is coated with an aqueous polyurethane adhesive with nanodiamonds added thereto, the mass volume ratio of nanodiamonds to aqueous polyurethane adhesive is 5g:80mL, and the composite material including the inner heat conductive layer and the outer layer is obtained by curing and drying at 70°C for 15h.
[0155] Step 3: Treat the outer layer with dilute hydrochloric acid to remove the nano-calcium carbonate, and obtain an outer heat dissipation layer having both nanopores and micropores, thereby obtaining a lightweight and high heat dissipation PC composite material.
[0156] Comparative Example 3
[0157] In this embodiment, PC, ABS and magnesium stearate are directly used as raw materials to prepare a composite material.
[0158] Performance Testing:
[0159] The composite materials of each embodiment, the composite materials of comparative example 3 and the inner heat conductive layer directly prepared in embodiment 3 were prepared into a new energy battery box, and the battery temperature and the box surface temperature were measured at room temperature 25°C after the battery worked for 0.5h, 2h, 5h and 20h. The results are shown in Table 2 below:
[0160] Table 2
[0161]
Claims
1. A lightweight and high heat dissipation PC composite material, characterized in that: It includes an inner heat-conducting layer and an outer heat-dissipating layer; the inner heat-conducting layer has a thickness of 0.5-3.0 mm, and the outer heat-dissipating layer has a thickness of 0.05-0.1 mm; The preparation method of the inner heat conductive layer is as follows: Step 1: Mix the foamed aluminum nitride particles with silver nanowires on the surface and nanodiamonds, add the hydrolyzed silane coupling agent, and stir to react for 4-5 hours; Step 2: Filter and dry to obtain mixed filler; Step 3: Dry 100 parts of PC and 35 parts of ABS, add 10-15 parts of mixed filler and 5 parts of magnesium stearate, and mix well in a high-speed mixer; Step 4: Extrusion granulation through a twin-screw extruder, the extrusion temperature is 220-250°C, the screw speed is 60r / min, and lightweight and high thermal conductivity granules are obtained; Step 5: Dry at 100°C, and use an injection molding machine with an injection temperature of 225-260°C to obtain an inner heat conductive layer; The preparation method of the foamed aluminum nitride particles having silver nanowires on the surface is as follows: Mix 10 parts of 0.5 mmol / L silver nitrate aqueous solution and 10 parts of 0.5 mmol / L sodium citrate aqueous solution, stir vigorously, quickly add 0.6 parts of 10 mmol / L sodium borohydride solution, and stop stirring after 30 seconds. A suspension of silver nanoparticles with a diameter of 2-6 nm is obtained; Take 3 parts of foamed aluminum nitride particles, add them into a mixed solution of 150 parts of 1 mmol / L silver nitrate and 2 mmol / L polyvinyl pyrrolidone, and stir evenly; Add 5-7 parts of silver nanoparticle suspension and stir for 0.5h; Irradiate under a 15 W low-pressure mercury lamp with a wavelength of 253.7 nm for 48 h; Filtering to obtain foamed aluminum nitride particles with silver nanowires on the surface; The preparation method of the above-mentioned lightweight and high heat dissipation PC composite material comprises the following steps: Step 1: Dissolve 10-15 parts of PC in 100 parts of chloroform, add 1-2 parts of nano calcium carbonate, stir for 3-4 hours to obtain electrospinning solution; Step 2: transferring the electrospinning solution to an electrospinning device, and performing electrospinning with the inner heat conductive layer as a receiving plate, wherein the receiving spinning surface of the inner heat conductive layer is coated with a hydrophilic adhesive added with nano-diamonds, and curing and drying at 60-80° C. for 10-18 hours to obtain a composite material including an inner heat conductive layer and an outer layer; Step 3: Treat the outer layer with dilute hydrochloric acid to remove the nano-calcium carbonate, and obtain an outer heat dissipation layer having both nanopores and micropores, thereby obtaining a lightweight and high heat dissipation PC composite material.
2. A lightweight and high heat dissipation PC composite material according to claim 1, characterized in that: In step 1, the mass ratio of the foamed aluminum nitride particles having silver nanowires on the surface to the nano-diamonds is (1-2):
1.
3. The lightweight and high heat dissipation PC composite material according to claim 1, characterized in that: The foamed aluminum nitride particles have a particle size of 10-50 μm and a porosity of 74-76%.
4. The lightweight and high heat dissipation PC composite material according to claim 1, characterized in that: The particle size of the nano calcium carbonate is 30-60nm.
5. The lightweight and high heat dissipation PC composite material according to claim 1, characterized in that: The electrospinning parameters are as follows: the spinning temperature is 22-28° C., the spinning voltage is 14-18 kV, the relative humidity is 40-50%, the receiving distance between the receiving plate and the electrospinning nozzle device is 10-14 cm, and the spinning solution flow rate is 1.0-1.5 mL / h.
6. The lightweight and high heat dissipation PC composite material according to claim 1, characterized in that: The mass volume ratio of nano-diamond to hydrophilic adhesive in the hydrophilic adhesive added with nano-diamond is (3-5) g:80 mL.
7. The lightweight and high heat dissipation PC composite material according to claim 5, characterized in that: The inner diameter of the electrospinning nozzle is 0.4-0.6 mm.
